Reforming Digital Mapping Regulations for Preventing Spatial Planning Violations in Indonesia: A Lesson from Australia - Widiatedja, I Gusti Ngurah Parikesit; Hosen, Nadirsyah; Yasa, Putu Gede Arya Sumerta; Arsika, I Made Budi; Shara, Made Cinthya Puspita (Journal of Indonesian Legal Studies, 2024)
Digital maps of the detailed plans play a crucial role in enforcing spatial planning regulations, providing clarity on permissible areas and assisting authorities in ensuring adherence. Despite existing regulations, violations are common, notably in Bali's tourism sector. The Job Creation Law 2023 then mandates accessible digital map issuance for detailed plans, integrating them into online submission systems to enhance transparency. Nonetheless, challenges persist, with many plans awaiting conversion into maps, underscoring the ongoing need for procedural efficiency in Indonesia. In Australia, local governments oversee planning decisions, with state involvement in strategic planning, exemplified by Victoria's governance under the Planning and Environmental Act 1987. Planning schemes that contain digital maps, determine land use rules, often categorized into zones with various permit requirements. Victoria's adoption of the smart planning initiative aims to improve accessibility and engagement through user-friendly digital platforms. By looking at Australia’s practices, this paper finds that Indonesia should address regulatory, technical, and coordination challenges, alongside prioritizing public involvement and professional cooperation in order to enhance Indonesia's digital map issuance processes and promote more effective spatial planning governance.